2016
DOI: 10.1111/liv.13303
|View full text |Cite
|
Sign up to set email alerts
|

17,β‐estradiol inhibits hepatitis C virus mainly by interference with the release phase of its life cycle

Abstract: Background & AimsOestrogen and oestrogen‐mediated signalling protect from hepatitis C virus through incompletely understood mechanisms. We aimed to ascertain which phase(s) of hepatitis C virus life cycle is/are affected by oestrogens.MethodsHuh7 cells infected with the JFH1 virus (genotype 2a) were exposed to dehydroepiandrosterone, testosterone, progesterone and 17β‐estradiol (tested with/without its receptor antagonist fulvestrant). Dose–response curves were established to calculate half maximal inhibitory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…Those effects would be related to both ERs and GPER. Finally, our findings would support clinical observations about the different evolution of hepatic fibrosis in postmenopausal women or men versus premenopausal women and about the delay that hormone replacement therapy with estrogen would cause cirrhosis evolution in postmenopausal women [2, 5, 45]. …”
Section: Discussionsupporting
confidence: 74%
“…Those effects would be related to both ERs and GPER. Finally, our findings would support clinical observations about the different evolution of hepatic fibrosis in postmenopausal women or men versus premenopausal women and about the delay that hormone replacement therapy with estrogen would cause cirrhosis evolution in postmenopausal women [2, 5, 45]. …”
Section: Discussionsupporting
confidence: 74%
“…Moreover, castrated male mice did not show an increase in death number due to SARS‐CoV infection compared to the control group, suggesting that the susceptibility to SARS‐CoV severity could be sex‐related, and estrogen may play an important role in the disease onset. Adding another perspective, it has been demonstrated that 17β‐estradiol interferes with hepatitis C life cycle (Magri et al, 2017), suggesting a direct mechanism of steroid action on virus, rather than only by modulating host intracellular homeostatic processes. Moreover, sterols have been suggested to potentially modify virus infection capacity (Rezanka et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The worse outcome of HCV infection in men may also be explained by the direct influence of sex hormones on HCV itself. 17β-estradiol was found to inhibit production of mature HCV virions, through ERα binding ( 65 , 66 ) and to inhibit HCV entry, through down-regulation of occludin (one of the receptors used by HCV to access the hepatocytes), in infected cell cultures ( 67 ).…”
Section: Sex Disparity In Hepatitis B Virus (Hbv) and Hepatitis C Virmentioning
confidence: 99%